Trump’s Call to Control Gaza: A Case of Ethnic Cleansing? - Muhammad Fathi; Muhammad Nur Rifqi Amirullah; Rian Ade Pangestu (Fakultas Hukum Universitas Lampung, 2025)
This research examines the intersection of international law and the controversial proposal by former US President Donald Trump regarding the forced transfer of Palestinian civilians from Gaza. The study places this issue within the framework of ethnic cleansing and the prohibition of population transfer under international humanitarian law, aiming to assess whether such a proposal may violate international law, particularly the Geneva Conventions and customary international law. Using a normative juridical method with conceptual and statutory approaches, the analysis draws on key legal instruments, including the Fourth Geneva Convention, the Rome Statute, and United Nations resolutions, to evaluate the legality of forced displacement in armed conflict. The findings indicate that Trump's statements, although lacking legal authority, risk legitimizing practices that could constitute ethnic cleansing or crimes against humanity if implemented. The study also highlights the broader implications of such rhetoric for state responsibility, international criminal accountability, and the weakening of protective norms. It concludes that the international community must reject policies that normalize forced transfer and consistently enforce international obligations to prevent impunity and protect civilian populations.